Acute effects of lead on porcine neonatal Sertoli cells in vitro. (April 2018) - Mancuso, Francesca; Arato, Iva; Lilli, Cinzia; Bellucci, Catia; Bodo, Maria; Calvitti, Mario; Aglietti, Maria Chiara; dell'Omo, Marco; Nastruzzi, Claudio; Calafiore, Riccardo; Luca, Giovanni; Marinucci, Lorella
Abstract: Environmental pollution is one of the main factors responsible for reducing fertility in males. Lead is one of the major heavy metal contaminants that impairs several organs; it preferentially accumulates in male reproductive organs and alters sperm quality both in vivo and in vitro . However, the underlying mechanisms remain unclear. Sertoli cells (SCs) provide structural and physiological support to spermatogenic cells within seminiferous tubules. Therefore, changes in SCs affect the developing germ cells and alter spermatogenesis. This study aimed to assess whether exposure to subtoxic doses of adversely affects SC functioning in higher mammals. Purified and functional porcine neonatal SCs were exposed to lead acetate at three different concentrations. Lead exposure decreased the mRNA expression and protein levels of inhibin B and anti-Mullerian hormone (AMH) compared to control, indicating loss of FSH-r integrity in terms of 17-β-oestradiol production under FSH stimulation. In addition, we observed an increase in the mRNA levels of Akt and mTOR, and the phosphorylation of p38 and Akt in SCs exposed to lead at all concentrations compared to unexposed control SCs. In conclusion, lead is toxic to SCs, even at low concentrations, and is expected to alter spermatogenesis. Highlights: Exposure of purified pig neonatal SC to toxic Pb concentrations was performed; Inhibin B and anti-Mullerian hormone (AMH) mRNAs and proteins were decreased; FSH-r integrity, in terms of 17-β-estradiol production, was decreased under FSH stimulation; We observed an increase of AKT and mTOR mRNAs, p38 and Akt phosphorylation ratio; Pb-related toxicity on SC, even at low concentrations, is expected to alter spermatogenesis.